1998
DOI: 10.1152/ajprenal.1998.275.2.f230
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of furosemide augments renal weight and glomerular capillary pressure in normal rats

Abstract: Angiotensin II (ANG II) is believed to promote progressive renal injury via augmented glomerular capillary hydraulic pressure (PGC). Acute volume reduction secondary to diuretic administration increases circulating ANG II and augments PGC, yet the hemodynamic effects of sustained diuretic administration are unknown. Therefore, glomerular micropuncture studies were performed in male Munich-Wistar rats after 6–8 wk of treatment with daily furosemide (F, 40 mg/day), furosemide plus the AT1 receptor antagonist, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…While some studies suggest an acute and probably direct relaxing effect of loop diuretics on venous tone, mean arterial blood pressure does not appear to be systematically altered in the short term before major salt losses have occurred (1,21,33,37). Furthermore, if the renal baroreceptor is located in the JGA region of the afferent arteriole, the renal vasodilatation typically seen with loop diuretics may cause an increase, not a decrease in pressure at the site of the baroreceptor, because it is well established that these agents cause an increase in glomerular capillary pressure (5,23,27). In addition, our studies in the isolated kidney show that the increase in perfusion flow rate caused by bumetanide is only between 5 and 10%, a change that is unlikely to be primarily responsible for the marked increase in renin release.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies suggest an acute and probably direct relaxing effect of loop diuretics on venous tone, mean arterial blood pressure does not appear to be systematically altered in the short term before major salt losses have occurred (1,21,33,37). Furthermore, if the renal baroreceptor is located in the JGA region of the afferent arteriole, the renal vasodilatation typically seen with loop diuretics may cause an increase, not a decrease in pressure at the site of the baroreceptor, because it is well established that these agents cause an increase in glomerular capillary pressure (5,23,27). In addition, our studies in the isolated kidney show that the increase in perfusion flow rate caused by bumetanide is only between 5 and 10%, a change that is unlikely to be primarily responsible for the marked increase in renin release.…”
Section: Discussionmentioning
confidence: 99%
“…Pappa2, an IGF-1 binding protein protease, known to increase IGF-1 bioavailability is up-regulated in TAL cells. Also, furosemide treatment increases the kidney-to-body weight ratio of rats 22,23,72 and now, mice, and the proximal tubule comprises the bulk of nephron mass (by immunofluorescence and flow cytometry, data not shown). Thus, we postulated that a furosemide-induced increase in proximal tubule cell size would be necessary and sufficient to increase kidney size.…”
Section: Discussionmentioning
confidence: 93%
“…Pappa2, an IGF-1 binding protein protease, known to increase IGF-1 bioavailability is up-regulated in TAL cells. Also, furosemide treatment increases the kidney-to-body weight ratio of rats 22,23,72 and now, mice, and the proximal tubule Egfr and Pten knockout mice, Harris and colleagues showed that tonic PI3-kinase signaling can override anti-proliferative genes in unstimulated kidneys 84 . In their model, unilateral nephrectomy further increased contralateral kidney size implying that additional pathways can generate a hypertrophic response.…”
Section: Igf-1 Signaling Hypertrophy and Kidney Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Glomerular hypertrophy has been pointed out as one of the initiating factors leading to the development of glomerulosclerosis (23,29), along with an elevation of P GC (5,17,18,31), presumably because these two abnormalities synergistically increase mechanical stretching of the glomerular wall (13), thus leading to glomerular cell proliferation and to the production of inflammatory mediators (21). The action of furosemide on P GC in the Nx model has not been examined, but it is noteworthy that P GC has been previously shown to be elevated in normal rats treated with furosemide for 6 -8 wk (33), raising the possibility that persistence of both tuft enlargement and intracapillary hypertension limited any renoprotective effect that the natriuretic action of furosemide might have provided. The mechanisms underlying these effects are unclear.…”
Section: Discussionmentioning
confidence: 99%